(untitled) (Hekima Review, 2024)
The opening of Hekima College in 1984 concluded adiscernment process in which Pedro Arrupe SJ played a key role.It also marked the beginning of the college’s journey to becominga school of theology. In the middle of the culmination and the beginningwas African theology, which determined the fruit of the ended discernmentand the destination of the started journey. This article discusses thishistory, proposing that African theology was the context into whichHekima was born and the mission it received from its founders. This wasin response to the post-World War II African reality that, by the 1970s, hadturned inculturation into an imperative on which depended the survivalof Christianity on the continent. At Hekima, theology was to answerquestions that Africans asked and solve problems and needs that Africansfelt. The article ends with a brief assessment of Hekima’s African-theologyperformance in the last forty years.